Penerapan Model Pembelajaran Kooperatif Tipe TGT (Teams Games Tournament) untuk Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Sosiologi Kelas Xl IPS 1 SMAN 1 Lubuk Basung - Lidiya Putri Handayani; Nurlizawati Nurlizawati (Universitas Negeri Padang, 2022)
This study aims to analyze the increase in learning motivation of students class XI IPS 1 SMAN 1 Lubuk Basung in sociology learning, by applying the Team Games Tournament (TGT) type cooperative model for the 2021/2022 academic year. To analyze the problems in this study, the researcher uses the learning theory by Thorndike which says that a response or learning process followed by pleasant conditions by giving gifts or praise will strengthen the learning process. This type of research is Classroom Action Research (CAR) with 26 research subjects in class XI IPS 1. The approach model used by Kemmis and Mc. Taggart which consists of four components: planning (planning), action (acting), observation (observation), reflection (reflecting). The data collection technique used is observation and interviews. The research instrument used in this research is an observation sheet. Analysis Techniques Observational data used quantitative descriptive data analysis techniques.The results showed that from the analysis of observational data in the study of increasing learning motivation with the application of the Team Games Tournament learning model, the students of class XI IPS 1 SMAN 1 Lubuk Basung experienced an increase. The highest increase is that it is not easy to let go of things that are believed from 50% in the first cycle to 90.38% in the second cycle, this is because. Can maintain the opinion of 55.76% to 88.45% in the second cycle. This can be seen from the activeness of students in expressing opinions in class or students who ask and provide questions about the material being studied, these active students are also influenced by the additional value given by the teacher if they are active in the learning process. The difference in the average increase from the first cycle to the second cycle is 26.51%. The average in the first cycle from 58.40% to 73.89% in the second cycle. The conclusion that can be drawn from this discussion is that by applying the Team Games Tournament (TGT) type of cooperative learning model, it can increase students' motivation to learn sociology in class XI IPS 1 SMAN 1 Lubuk Basung.